2020
DOI: 10.1002/jbt.22527
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviated H2O2‐induced apoptosis and steroidogenic impairment in goat luteinized granulosa cells

Abstract: Quercetin (Que) is a natural flavonoid in most plants. Luteinized granulosa cell (LGC) culture is necessary for the study of follicle growth/differentiation. In the present study, we analyzed the role of Que in steroid production and apoptosis in hydrogen peroxide (H2O2)‐treated goat LGCs. The results showed that treatment with H2O2 induced apoptosis in goat LGCs, and treatment with Que decreased LGC apoptosis induced by H2O2 (P < .05), accompanied with the different expressions of BAX, BCL‐2, Caspase 3, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Hydrogen peroxide induced oxidative stress in granulosa cells, and then 20 μM QUR intervention showed that reactive oxygen species (ROS) decreased, NF-E2-related factor 2 (Nrf2) and thioredoxin (Trx) increased, thereby cell damage was repaired. Similar results were seen in granulosa cells of goats and bovines (Khadrawy et al, 2019;Li et al, 2020). In Cadmium-induced chicken granulosa cells, QUR increased X-linked inhibitor of apoptosis protein (XIAP) and decrease caspase-3 and ROS (Jia et al, 2011).…”
Section: In Vitro Studies Of Qur On Ovarian Cellssupporting
confidence: 71%
See 2 more Smart Citations
“…Hydrogen peroxide induced oxidative stress in granulosa cells, and then 20 μM QUR intervention showed that reactive oxygen species (ROS) decreased, NF-E2-related factor 2 (Nrf2) and thioredoxin (Trx) increased, thereby cell damage was repaired. Similar results were seen in granulosa cells of goats and bovines (Khadrawy et al, 2019;Li et al, 2020). In Cadmium-induced chicken granulosa cells, QUR increased X-linked inhibitor of apoptosis protein (XIAP) and decrease caspase-3 and ROS (Jia et al, 2011).…”
Section: In Vitro Studies Of Qur On Ovarian Cellssupporting
confidence: 71%
“…11 in vitro studies (Jia et al, 2011;Capcarova et al, 2015;Tarko et al, 2018;Sirotkin et al, 2019a;Sirotkin et al, 2019b;Khadrawy et al, 2019;Kolesarova et al, 2019;Rashidi et al, 2019;Li et al, 2020;Yang et al, 2021b;Davoodian et al, 2022) have been included and are shown in Table 1. The cell origin, in vitro model, QUR dosage and biological response have been reviewed.…”
Section: In Vitro Studies Of Qur On Ovarian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that cleaved caspase 3 and cleaved PARP are important modulators in cell growth. [16][17][18] Huang et al indicated that cleaved caspase 3 is a pro-apoptotic protein. 19 Additionally, cleaved PARP can also be upregulated during the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is a flavonoid with a wide range of biological activities such as antioxidation, anti-apoptosis, and antiinflammation [53][54][55][56]. It has been reported that QUE protects granulosa cells from damage caused by oxidative stress in pigs [25], goats [57], buffaloes [28], and chickens [58]. Moreover, QUE alleviates the toxic effects of heavy metals such as copper [59], cadmium [60], cisplatin [61], iron [62], and lead [63].…”
Section: Discussionmentioning
confidence: 99%